JOHN LOUIS ESPOSITO TENTANG DIALOG PERADABAN ISLAM-BARAT - Hamdani, Moh. Salman (Fakultas Dakwah IAIN Purwokerto, 2013)
This paper aims to provide explanation about John Louis Esposito’s insights on therelationship between Islam and The West. The relationship is a fluctuative one, some tensionsand even open conflict may occur. Some events become the entry point to the relationship, forinstance, the crusades that is not only happened physically but also, through this war, the meetingbetween Islam and The West establishes inter cultural dialogue among them.John Louis Esposito’s views on the relationship between Islam and The West ispositioned in view of some Muslim intellectuals and orientalists to emphasize its originality. Theintellectual positions do not put it on pros or cons side in the context of the relationship betweenIslam and The West.Historically, the relationship between Islam and The West actually has a theologicallystrong bond that there is common ground and similarities between Islam and The West. Islamand The west are inherited with Jewish and Christian traditions. Islam like Christianity andJudaism are religions ‘of the sky’ that are allied in Abrahamic religions. Therefore, according toJohn L. Esposito, based on historical fact, there were a real strong bond between Islam and theWest and it started centuries ago .